Perinatal outcome in pregnancies complicated with oligohydramnios at term - Bhaskar Suneetha, Kambham; Parvathaneni, Silpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: AFI of less than or equal to five cm is considered oligohydramnios. Various approaches, such as NST, acoustic stimulation, and foetal Doppler velocimetry, are useful in assessing foetal well-being and identifying pregnancies at risk of postnatal complications. The goal of this study was to learn about the negative perinatal outcomes in pregnant women who had oligohydramnios at term and to assess the efficacy of AFI in predicting foetal distress and caesarean delivery. Methods: A retrospective and comparative study of singleton pregnancies outcomes in 60 women diagnosed with oligohydramnios by USG after 37 weeks of pregnancy, compared to 60 women who did not have oligohydramnios and were matched for other factors. Some criteria for inclusion and exclusion were utilised. The data was analysed using statistical criteria such as mean, standard deviation, and chi square test sensitivity, specificity, PPV, and NPV. Results: The occurrence of non-reactive and re-active NST patterns differed significantly between the two groups. In comparison to women with AFI >5 cm, women with AFI 5cm have a higher rate of labour induction. LBW (2.5 kg) was more common in women with oligohydramnios, and LSCS rates were higher in oligohydramnios-complicated pregnancies. Conclusions: After 37 weeks of pregnancy, an AFI of less than 5 cm is a sign of poor perinatal outcome. AFI can be used in conjunction with other foetal monitoring techniques. AFI is a useful screening test for predicting foetal distress during labour that necessitates a caesarean section.